2012
DOI: 10.1128/mcb.00827-12
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles of Da Transactivation Domains in Neurogenesis and in E(spl)-Mediated Repression

Abstract: E proteins are a special class of basic helix-loop-helix (bHLH) proteins that heterodimerize with many bHLH activators to regulate developmental decisions, such as myogenesis and neurogenesis. Daughterless (Da) is the sole E protein in Drosophila and is ubiquitously expressed. We have characterized two transcription activation domains (TADs) in Da, called activation domain 1 (AD1) and loop-helix (LH), and have evaluated their roles in promoting peripheral neurogenesis. In this context, Da heterodimerizes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 78 publications
(103 reference statements)
2
27
0
Order By: Relevance
“…We found that the DPY-22 PQ-rich domain selectively interacted with HLH-2 but not HLH-3, whereas the last 129 amino acids truncated in all five dpy-22 alleles were required for this interaction (Figure 4B). Further analysis indicated that the PQ-rich domain interacted with the N-terminal half of HLH-2, the region of a predicted transactivation domain important for gene expression and neurogenesis [36, 37] (Figure 4C). These findings suggest that Mediator physically interacts with and might function in the same pathway as HLH-2 to promote I4 neurogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the DPY-22 PQ-rich domain selectively interacted with HLH-2 but not HLH-3, whereas the last 129 amino acids truncated in all five dpy-22 alleles were required for this interaction (Figure 4B). Further analysis indicated that the PQ-rich domain interacted with the N-terminal half of HLH-2, the region of a predicted transactivation domain important for gene expression and neurogenesis [36, 37] (Figure 4C). These findings suggest that Mediator physically interacts with and might function in the same pathway as HLH-2 to promote I4 neurogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…We were able to restore degradation of Sc[1–320] by m7 when we fused the AD1 domain of Da in place of the Sc TAD (Supplementary Figure S5F and G), since AD1 also strongly interacts with m7 via the latter's Orange domain (68). Fusion of a non-interacting TAD, the Da LH, did not restore Sc[1–320] degradation (Supplementary Figure S5G).…”
Section: Resultsmentioning
confidence: 99%
“…Like the HLH domain, the Orange domain consists of two amphipathic alpha-helices and mediates protein-protein interactions, including dimerization of the basic helix-loop-helix-orange (bHLH-O) proteins, where it acts as an "extension" of the HLH domain (Dawson, Turner, Weintraub, & Parkhurst, 1995;Eastwood, Yin, Bandyopadhyay, & Bidwai, 2011;Knust et al, 1992;Taelman et al, 2004;Zarifi et al, 2012). Like the HLH domain, the Orange domain consists of two amphipathic alpha-helices and mediates protein-protein interactions, including dimerization of the basic helix-loop-helix-orange (bHLH-O) proteins, where it acts as an "extension" of the HLH domain (Dawson, Turner, Weintraub, & Parkhurst, 1995;Eastwood, Yin, Bandyopadhyay, & Bidwai, 2011;Knust et al, 1992;Taelman et al, 2004;Zarifi et al, 2012).…”
Section: E(spl): From a Spontaneous Dominant Mutation To A Group Of Cmentioning
confidence: 99%
“…This system explicitly illustrates the antagonism between AS-C proneural proteins and E(spl), for example, by their diametrically opposite lof and gain-of-function (gof ) phenotypes. Whereas the naturally basic-less HLH protein Extramacrochetae (Emc, homolog of vertebrate Id) interacts with Da and proneural proteins using the HLH helices and in doing so averts their DNA binding (Van Doren, Ellis, & Posakony, 1991), E(spl) proteins neither use their HLH helices to interact with proneurals nor do they abolish proneural DNA binding (Giagtzoglou et al, 2003(Giagtzoglou et al, , 2005Zarifi et al, 2012). Reciprocally, overexpression of any of the three AS-C genes causes overproduction of bristles, whereas overexpression of any of the seven E(spl) genes causes reduction or complete elimination of bristles (Giebel & Campos-Ortega, 1997;Hinz, Giebel, & Campos-Ortega, 1994;Ligoxygakis, Bray, Apidianakis, & Delidakis, 1999;Tata & Hartley, 1995).…”
Section: Lateral Inhibition Of Neural Precursors In the Pns-inhibitiomentioning
confidence: 99%
See 1 more Smart Citation